When languages die : the extinction of the world's languages and the erosion of human knowledge - Harrison, K. David (Oxford ; New York : Oxford University Press, 2007)
In When Languages Die, K. David Harrison illustrates the individual face of language loss, as well as its global scale. Languages are the accretion of thousands of years of a peoples science and art - from observations of ecological patterns to creation myths. The author shows that the disappearance of a language is a loss not only for the community of speakers itself but also for our common human knowledge of mathematics, biology, geography, philosophy, agriculture, and linguistics. In this century, we face a massive erosion of the human knowledge base. The global abandonment of indigenous languages will bring a massive loss of accumulated knowledge and culture - this book argues for the irreplaceable nature of these unique knowledge systems and the urgency of documenting them before they are lost forever. Book jacket.
Includes information on Australia, calendars, creation myths, directions, epics, fish, folksonomy, genetics, grammar, Himalayan mountains, horse, indigenous people, knowledge, literacy, maps, metaphor, months, naming, nomads, oral traditions, Os (middle Chulym), Papua New Guinea, place names, reindeer, rivers, shamans, sign languages, singing, song, species, taxonomy, units of time, time reckoning, Tofa (Tofalar, Karagas), Tuvan, writing systems, Yukaghir, etc.
1 A World of Many (Fewer) Voices -- 2 An Extinction of (Ideas about) Species -- Case Study: Vanishing Herds and Reindeer Words -- 3 Many Moons Ago: Traditional Calendars and Time-Reckoning -- Case Study: Nomads of Western Mongolia -- 4 An Atlas in the Mind -- Case Study: Wheel of Fortune and a Blessing -- 5 Silent Storytellers, Lost Legends -- Case Study: New Rice versus Old Knowledge -- 6 Endangered Number Systems: Counting to Twenty on Your Toes -- Case Study: The Leaf-Cup People, India's Modern Primitives -- 7 Worlds within Words.
Bibliografija: str. 263-283 i kazalo.
Keywords: izumiranje jezika -- nestanak jezika -- ugroženi jezici